Evidence that Certain Clones of Campylobacter jejuni Persist during Successive Broiler Flock Rotations - Petersen, L. (American Society for Microbiology, 2001)
Through the national surveillance program for Campylobacter spp., nine broiler chicken farms that were infected with Campylobacter jejuni in at least five rotations in 1998 were identified. One additional farm, located at the island of Bornholm where divided slaughter is used extensively, was also selected. Twelve broiler houses located on 10 farms were included in the study. The C. jejuni isolates collected from the selected houses during the surveillance were typed using fla typing and macrorestriction profiling (MRP), and a subset of the isolates, representing each of the identified clones, was serotyped according to the Penner scheme. Pulsed-field gel electrophoresis typing using SmaI and KpnI revealed that the majority of houses (11 of 12) carried identical isolates in two or more broiler flocks. Such persistent clones were found in 63% of all flocks (47 of 75). The majority of persistent clones (7 of 13) had fla type 1/1, but MRPs distinguished between isolates from different houses, and fla type 1/1 clones belonged to different serotypes. Seven houses carried persistent clones that covered an interval of at least four broiler flock rotations, or at least one half year. The dominant fla type (1/1) was represented by 44% of isolates, or by at least one isolate from 31 of 62 broiler flocks. This significantly exceeded the prevalence of fla type 1/1 C. jejuni isolates that we have estimated from other studies and suggests that isolates carrying this fla type are overrepresented in flocks with recurrent Campylobacter problems. The MRPs of clones belonging to fla type 1/1 serotype O:2 isolated from persistently infected flocks shared a high percentage of bands compared to the remaining isolates, indicating that some clones that have the ability to cause persistent infections in broiler farms are highly related to each other.